Discordance in CD4+T-cell levels and viral loads with co-occurrence of elevated peripheral TNF-α and IL-4 in newly diagnosed HIV-TB co-infected cases. - Ronald Benjamin; Atoshi Banerjee; Sharada Ramaseri Sunder; Sumanlatha Gaddam; Vijaya Lakshmi Valluri; Sharmistha Banerjee (PLoS ONE, 2013)
BACKGROUND: Cytokines are the hallmark of immune response to different pathogens and often dictate the disease outcome. HIV infection and tuberculosis (TB) are more destructive when confronted together than either alone. Clinical data related to the immune status of HIV-TB patients before the initiation of any drug therapy is not well documented. This study aimed to collect the baseline information pertaining to the immune status of HIV-TB co-infected patients and correlate the same with CD4+T cell levels and viral loads at the time of diagnosis prior to any drug therapy. METHODOLOGY/PRINCIPAL FINDINGS: We analyzed the cytokines, CD4+T cell levels and viral loads to determine the immune environment in HIV-TB co-infection. The study involved four categories namely, Healthy controls (n=57), TB infected (n=57), HIV infected (n=59) and HIV-TB co-infected (n=57) patients. The multi-partite comparison and correlation between cytokines, CD4+T-cell levels and viral loads prior to drug therapy, showed an altered TH1 and TH2 response, as indicated by the cytokine profiles and skewed IFN-γ/IL-10 ratio. Inadequate CD4+T cell counts in HIV-TB patients did not correlate with high viral loads and vice-versa. When compared to HIV category, 34% of HIV-TB patients had concurrent high plasma levels of IL-4 and TNF-α at the time of diagnosis. TB relapse was observed in 5 of these HIV-TB co-infected patients who also displayed high IFN-γ/IL-10 ratio. CONCLUSION/SIGNIFICANCE: With these studies, we infer (i) CD4+T-cell levels as baseline criteria to report the disease progression in terms of viral load in HIV-TB co-infected patients can be misleading and (ii) co-occurrence of high TNF-α and IL-4 levels along with a high ratio of IFN-γ/IL-10, prior to drug therapy, may increase the susceptibility of HIV-TB co-infected patients to hyper-inflammation and TB relapse.